2016
DOI: 10.1039/c6cp04581b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning thermal transport in Si nanowires by isotope engineering

Abstract: We study thermal transport in isotopically disordered Si nanowires, discussing the feasibility of phonon engineering for thermoelectric applications within these systems. To this purpose, we carry out atomistic molecular dynamics and nonequilibrium Green's function calculations to characterize the dependence of the thermal conductance as a function of the isotope concentration, isotope radial distribution and temperature. We show that a reduction of the conductivity of up to 20% can be achieved with suitable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The thermal conductivity of a material must be high to keep a low thermal budget in a nanoscale device [3], for instance, while it should be as low as possible when it comes to the engineering of an efficient thermoelectric [4,5]. The thermal conductivity can be tuned to some extent by nanostructuring, adding defects [6,7], or designing periodic superstructures [8,9], but it would be desirable to be able to dynamically modify it. Besides an increased flexibility in materials design, this would also open the way to heat-based signal processing and computing [10].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity of a material must be high to keep a low thermal budget in a nanoscale device [3], for instance, while it should be as low as possible when it comes to the engineering of an efficient thermoelectric [4,5]. The thermal conductivity can be tuned to some extent by nanostructuring, adding defects [6,7], or designing periodic superstructures [8,9], but it would be desirable to be able to dynamically modify it. Besides an increased flexibility in materials design, this would also open the way to heat-based signal processing and computing [10].…”
Section: Introductionmentioning
confidence: 99%
“…It provides a very efficient and robust method to investigate thermal properties in a wide range of system sizes. AEMD has been applied by several authors to the calculation of the thermal conductivity in c-Si,c-Ge and α-quartz [1], in Si/Ge nanocomposite [9], in Si nanowires [10] and in graphene-based structures [11,12]. Initially developed for classical Molecular Dynamics (MD) this technique has been recently implemented in ab-initio calculations as well [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a curve of thermal conductivity vs. the concentration of doping isotope atom (x) is exhibited, which shows a similar tendency with Si x Ge 1−x and a plateau at 0.2 <x<0.8 (We will discuss this tendency in the next section). More simulations have been conducted for the isotope effect on thermal conductivity, like the isotopic core-shell Si NWs (Hattori and Uno, 2013) and isotope radial distribution (Royo and Rurali, 2016). The fabrication of Si isotope NWs is demonstrated in Mukherjee et al (2015) using the VLS method and a 30% decrease of thermal conductivity is shown in isotopically mixed 28 Si 30…”
Section: Si Nwsmentioning
confidence: 99%